Tuna Fish As A Source Of Inspiration For Ideas In The Creation Of Paintings - Gangga, I Putu Bisma Maha; Adnyana, I Wayan; Utami, Ni Made Purnami (Program Studi Seni Murni ISI Bali, 2025)
The final report of this independent study/project raises the theme